Mental health recovery and physical health outcomes in psychotic illness: Longitudinal data from the Western Australian survey of high impact psychosis catchments. (July 2021) - Morgan, Vera A; Waterreus, Anna; Ambrosi, Taryn; Badcock, Johanna C; Cox, Kay; Watts, Gerald F; Shymko, Gordon; Velayudhan, Ajay; Dragovic, Milan; Jablensky, Assen
Objective: There is a dearth of longitudinal data on outcomes in prevalent cases of psychotic illness across a range of ages and levels of chronicity. Our aim was to describe changes over time in mental and physical health outcomes, as well as patterns of service utilisation that may have influenced outcomes, in a representative prevalence sample of 641 Western Australians with a psychotic illness who, at Wave 1, were part of the National Survey of High Impact Psychosis. Methods: In Wave 1 (2010, 2012), a two-phase design was employed to ensure representativeness: Phase 1 psychosis screening took place in public mental health and non-government organisation services, while, in Phase 2, a randomised sample was interviewed. In Wave 2, 380/641 (59%) of participants were re-interviewed, with interviews staggered between 2013 and 2016 (follow-up time: 2.3–5.6 years). Data collection covered mental and physical health, functioning, cognition, social circumstances and service utilisation. Mental health outcomes were categorised as symptomatic, functional and personal recovery. Physical health outcomes covered metabolic syndrome and its component criteria. Results: In mental health, there were encouraging improvements in symptom profiles, variable change in functional recovery and some positive findings for personal recovery, but not quality of life. Participants ranked physical health second among challenges. Metabolic syndrome had increased significantly. While treatment for underlying cardiovascular risk conditions had improved, rates of intervention were still very low. More people were accessing general practices and more frequently, but there were sharp and significant declines in access to community rehabilitation, psychosocial interventions and case management. Conclusion: Although we observed some positive outcomes over time, the sharp decline in access to evidence-based interventions such as community rehabilitation, psychosocial interventions and case management is of great concern and augurs poorly for recovery-oriented practice. Changes in service utilisation appear to have influenced the patterns found.